(untitled) (International journal of artificial intelligence, 2026)
This article examines the development of students’ computer-aided design competence through the use of the “Rotate” and “Mirror” commands in AutoCAD during engineering graphics instruction. The results of the pedagogical experiment show that systematic application of these commands improves spatial thinking, drawing accuracy, and task performance speed.